2015
DOI: 10.1039/c5tc02732b
|View full text |Cite
|
Sign up to set email alerts
|

The DNA strand assisted conductive filament mechanism for improved resistive switching memory

Abstract: The DNA strand assisted conductive filament mechanism is suggested to explain the resistive switching behaviors of the Au/CuO-DNA-Al/Au/Si device.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(38 citation statements)
references
References 58 publications
1
37
0
Order By: Relevance
“…ECMMs utilize electrochemically active electrodes as TE and electrochemically inert electrodes as BE . The RS process in the switching layer involves three steps, i.e., oxidation of the metal electrode, migration, and reduction of metal cations.…”
Section: Ionotronic Memristorsmentioning
confidence: 99%
“…ECMMs utilize electrochemically active electrodes as TE and electrochemically inert electrodes as BE . The RS process in the switching layer involves three steps, i.e., oxidation of the metal electrode, migration, and reduction of metal cations.…”
Section: Ionotronic Memristorsmentioning
confidence: 99%
“…This may be because conductive particles contribute to the formation of conductive laments and electron transport. [38][39][40] We also studied the resistance of the HRS and LRS of the doped device, as shown in Fig. 6b.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the electric switching characteristics of the devices, the measured I–V data were further analyzed in detail using various conduction models, including Ohmic conduction, Schottky emission, Poole–Frenkel emission, tunnel or emission, hopping conduction, space‐charge‐limited current (SCLC) conduction, and thermionic emission . However, it is found that any individual conduction mechanism mentioned above cannot fit well the characteristics for both the ON state and the OFF state at the same time, which suggests the involvement of probably different charge transport processes in the two conduction states …”
Section: Resultsmentioning
confidence: 99%